1967
DOI: 10.1002/1097-0142(1967)20:3<333::aid-cncr2820200302>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Daunomycin, an antitumor antibiotic, in the treatment of neoplastic disease.Clinical evaluation with special reference to childhood leukemia

Abstract: Daunomycin is a new antibiotic in the anthracycline group obtained from Streptomyces peucetius. It consists of a pigmented aglycone (daunomycinone) in glycoside linkage with an amino sugar (daunosamine). Differences in the biological effects of daunomycin, which reacts with DNA, and actinomycin D which complexes with DNA in a different manner to inhibit RNA production, are discussed. The toxic effects of daunomycin are a severe local reaction if the drug extravasates, bone marrow depression resulting in leucop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
166
0
10

Year Published

1969
1969
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 439 publications
(176 citation statements)
references
References 19 publications
0
166
0
10
Order By: Relevance
“…Detection of sub-clinical left ventricular dysfunction using imaging 1. LVEF as a tool to detect sub-clinical LV dysfunction Although the decrease in LVEF during treatment has been associated with symptomatic HF, 31,34,35 the ability of serial LVEF assessment during and after treatment to identify CTRCD and prevent subsequent HF remains controversial.…”
Section: Detection Of Sub-clinical LV Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of sub-clinical left ventricular dysfunction using imaging 1. LVEF as a tool to detect sub-clinical LV dysfunction Although the decrease in LVEF during treatment has been associated with symptomatic HF, 31,34,35 the ability of serial LVEF assessment during and after treatment to identify CTRCD and prevent subsequent HF remains controversial.…”
Section: Detection Of Sub-clinical LV Dysfunctionmentioning
confidence: 99%
“…Radionuclide approaches for monitoring chemotherapy-induced cardiotoxicity 1. MUGA Measurement of LV function using either first-pass or equilibrium radionuclide angiography (also known as MUGA) was first used in the late 1970s to identify patients receiving anthracyclines who had declines in LVEF before the development of clinical HF symptoms.…”
Section: Other Imaging Modalitiesmentioning
confidence: 99%
“…The first anthracycline isolated was daunorubicin (also called daunomycin), obtained from a bacterial strain of Streptomyces peucetius [2,3]. Another anthracycline also widely used in oncology is doxorubicin (Adriamycin ® ) [4].…”
Section: Introductionmentioning
confidence: 99%
“…During the course of therapy serious alterations were observed in both the e.c.g. and cardiac function (Tan et al, 1967 ;Malpas & Scott, 1969 ;Marmont et al, 1969). Experimentally, acute cardiac toxicity was demonstrated in the Syrian golden hamster (Herman et al, 1969) and confirmed in the rhesus monkey (Herman & Vick, 1970).…”
Section: Discussionmentioning
confidence: 99%